AuAg nanocomposites suppress biofilm-induced inflammation in human osteoblasts. (16th April 2023) - Lee, Chiang-Wen; Lin, Zih-Chan; Chiang, Yao-Chang; Li, Sin-Yu; Ciou, Jyun-Jia; Liu, Kuan-Wen; Lin, Yu-Ching; Huang, Bo-Jie; Peng, Kuo-Ti; Fang, Mei-Ling; Lin, Tzu-En; Liao, Mei-Yi; et al.
Abstract: Staphylococcus aureus (S. aureus) forms biofilm that causes periprosthetic joint infections and osteomyelitis (OM) which are the intractable health problems in clinics. The silver-containing nanoparticles (AgNPs) are antibacterial nanomaterials with less cytotoxicity than the classic Ag compounds. Likewise, gold nanoparticles (AuNPs) have also been demonstrated as excellent nanomaterials for medical applications. Previous studies have showed that both AgNPs and AuNPs have anti-microbial or anti-inflammatory properties. We have developed a novel green chemistry that could generate the AuAg nanocomposites, through the reduction of tannic acid (TNA). The bioactivity of the nanocomposites was investigated in S. aureus biofilm-exposed human osteoblast cells (hFOB1.19). The current synthesis method is a simple, low-cost, eco-friendly, and green chemistry approach. Our results showed that the AuAg nanocomposites were biocompatible with low cell toxicity, and did not induce cell apoptosis nor necrosis in hFOB1.19 cells. Moreover, AuAg nanocomposites could effectively inhibited the accumulation of reactive oxygen species (ROS) in mitochondria and in rest of cellular compartments after exposing to bacterial biofilm (by reducing 0.78, 0.77-fold in the cell and mitochondria, respectively). AuAg nanocomposites also suppressed ROS-triggered inflammatory protein expression via MAPKs and Akt pathways. The current data suggest that AuAg nanocomposites have the potential to be a good therapeutic agent in treating inflammation in bacteria-infected bone diseases.